Anesthetic management for cesarean section in chronic renal failure - Hemlata Kapoor; Kuzhupully Parambhil Krishnan; Kutty Rajeev (Journal of Obstetric Anaesthesia and Critical Care, 2014)
Pregnancy in chronic kidney disease is rare and is associated with high incidence of maternal and fetal morbidity. More women with chronic renal failure, due to better management and treatment modalities are able to conceive and carry on their pregnancy and delivery. The case report describes anesthesia for caesarean section in a parturient with chronic renal failure and reviews the literature.